Raise their voices: Rethinking the architect’s role in a colonial context such as mayotte through education and anti-racism - Pèpe, Fiona (My University, 2023)
It is nowadays essential for an architect to make her practice evolve since the society and its challenges are changing. It requires new radical approaches to answer issues that are no longer tolerable in the lives of people. For that, a critical architect needs to analyse, dismantle and propose new ways of working. As a legacy of the global expansion, territories are embedded in the colonization/ decolonization process. For that reason, the objective of this thesis is to look at the impact architects and architecture can have to support the decolonization process by rethinking the role of architects and architecture in the current society. It aims to explore how architects can raise awareness of the communities, towards the built environment as well as raising the voices of those who have been omitted in the architectural debate. That way, people will be able to engage and take responsibility for the context they live in. Therefore, the main research question of this thesis is: “HOW CAN ARCHITECTS REDEFINE THEIR ROLE TO BECOME SUPPORTERS IN THE DECOLONIZATION PROCESS AND ACT IN THE CONSTRUCTION OF AN ANTI-RACIST SOCIETY?” KEY WORDS: architecture; education; community; anti-racism; critical and dialogical pedagogy; methods; participation; diversity; inclusivity; community; sharing; collaboration This thesis’ research was based on two different focuses. The first one was to determine a strategy to guide the research development. This strategy was designed to debunk bias in order to avoid racism in the creation process. With the help of inspiring literature, this strategy is made out of four steps: [unlearn], [relearn], [reflect], [apply]. It has been used at a personal level to analyse several grounding concepts but also in the field study with the stakeholders. The second focus was a field study interaction. After several detours due to the reality of the field, the study case was about experimenting ways for the stakeholders to grasp their surrounding environment and restore their right to act towards it. For that, I have designed tools and workshops to encourage dialogue, which is the first fundamental step to conceive an inclusive built environment. The study case took place with teenagers in Mayotte an island in the Indian Ocean, torn between the states of Comoros and France. Three different influences, among others, have inspired the research: the work of Wai Think Tank, Paolo Freire and Achille Mbembe.
Keywords: architecture; education; community; anti-racism; critical and dialogical pedagogy; methods; participation; diversity; inclusivity; community; sharing; collaboration